2020
DOI: 10.1590/1809-4430-eng.agric.v40n1p113-120/2020
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Agronomic Performance and Soil Physical Attributes Under Tractor Traffic Intensities

Abstract: Machinery traffic intensification has been recurrent in intensive agriculture in annual crops, which may lead to structural soil degradation and, consequently, a reduction of its productive capacity. Therefore, this study aimed to assess the influence of tractor traffic intensification on soil physical attributes and soybean yield components. The study was performed in an Oxisol under no-tillage for 10 years, using a randomized block design with five tractor traffic intensities (0, 2, 4, 6, 8, and 12 passes) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(56 reference statements)
2
3
0
1
Order By: Relevance
“…The MRSP presents lower values in the planting rows, with FC having lower penetration resistance in both positions than TC. The results presented in this study show similarity with those obtained by Arcoverde et al (2020), who verified an increase in soil bulk density according to the machine traffic, finding soil bulk density averages between 1.36 and 1.50 Mg m -3 . It is also important to note that Bd is not very sensitive to the effects of traffic, so in some cases, the pressure exerted by machinery cannot modify it (Savioli et al, 2020).…”
Section: Resultssupporting
confidence: 90%
“…The MRSP presents lower values in the planting rows, with FC having lower penetration resistance in both positions than TC. The results presented in this study show similarity with those obtained by Arcoverde et al (2020), who verified an increase in soil bulk density according to the machine traffic, finding soil bulk density averages between 1.36 and 1.50 Mg m -3 . It is also important to note that Bd is not very sensitive to the effects of traffic, so in some cases, the pressure exerted by machinery cannot modify it (Savioli et al, 2020).…”
Section: Resultssupporting
confidence: 90%
“…These results corroborate those shown by ARCOVERDE et al (2020), who, in studying a dystroferric Red Latosol in a no-tillage system, observed similar density values in the same soil layers, restraining soybean grain productivity, therefore suggesting, according to the same authors, that surface soil compaction that does not restrict root growth can benefit crop production.…”
Section: Crop Production Componentssupporting
confidence: 90%
“…This shows that the increase in the number of tractor passes in a consolidated no-tillage system does not always result in an increase in compaction and reduction of soil structural quality, and even intermediate soil densification may benefit the productivity of crops (ARCOVERDE et al 2020, ARCOVERDE et al 2022, SUZUKI et al 2007). According to ARCOVERDE et al (2022), the intermediate densification in the 0.00-0.10 m layer, likely to have increased the volume of pores responsible for storing water in a voltage available for the plants.…”
Section: Soil Attribute Analysismentioning
confidence: 98%
See 2 more Smart Citations